A sustainable approach on thermal and catalytic conversion of waste plastics into fuels. (1st May 2023) - Senthil Rathi, B.; Senthil Kumar, P.; Rangasamy, Gayathri
Graphical abstract: Highlights: Production of the plastic waste is 34.7 lakh tonnes per annum and 50% is recycled. Sources, origin and impact of plastic waste has been reviewed. Different methods for the thermochemical conversion of plastic waste were elucidated. Sustainable products from plastic waste were explored. Circular Economy in handling of plastic waste were addressed. Abstract: Plastics have one of the highest rates of development due to its numerous uses, adaptability, and comparatively low cost. Due to the short average lifespan of plastic items, there is a significant annual flow of plastic garbage (34.7 lakh tonnes per annum (TPA)) to the ultimate consumers, which poses a substantial environmental threat. Recycled plastic makes up 50% of all generated plastic garbage and remaining retained as plastic waste (17 lakh tonnes per annum (TPA))). Again, there is a critical need for substitutes to dumping or land filling since regulations and growing costs are making it increasingly difficult to dispose of post-consumer plastics. Also, the conventional methods of burning and landfilling may result in environmental pollution and the waste of valuable land. This review highlighted the sources, kinds, and occurrence of plastic garbage in the atmosphere as well as its consequences on the environment and people. The study's first focus is on the origins and technique of thermochemical conversion of plastic waste. There has been discussion on the circular economy of plastic trash as well as the manufacturing of sustainable products from plastic garbage, such as oil, char, sorbent materials, fuels, and chemicals. An inventive additional method for producing such value-added goods from plastic trash is catalytic degradation. The potential for emissions, future technological advancement, and sustainability concerns were considered as potential downsides for thermochemical processes. To increase the production of value-added goods (fuel) with little investment and little impact on the environment, further research is needed. The report examines the body of literature that is currently accessible in this area of ongoing research and points out any gaps that require more investigation.